Military service and elite para ice hockey : a case study of American paralympians' sports paths - Ott, Kyra (2020)
This case study explores the influence military service had on American Para ice hockey players’ sports paths. The growing number of wounded veterans in America presents challenges and opportunities for elite Para sport talent development and support. Over the past ten years, USA Hockey has been able to establish a very successful Paralympic campaign by incorporating an ever-increasing number of veterans into their squad. An inductive-deductive research approach was chosen by utilizing the Sports Path Model by Aarresola (2016) as a theoretical framework for this sociological exploration of the factors influencing Para ice hockey players’ paths to Paralympic success. Semi-structured interviews were conducted with the two longest-serving veterans of the U.S. national team. The interviews were tape-recorded, transcribed verbatim, and analysed using thematic-content and frequency analysis. Results indicated that successful rehabilitation and sustainable elite Para sport careers of wounded veterans are closely linked to military support programs and their cooperation with elite Para sport organizations. They were termed institutional support networks. These networks were inextricably dependent on the individuals running and participating in the programs, building the athletes’ social capital, and giving them the ability to develop and exercise agency over time. Primarily, this study aims at giving valuable insight into successful talent development within elite Para sport. Secondarily, it attempts to outline the unique challenges that arise out of military backgrounds in sporting environments, thus, potentially supporting future talent development efforts.